VAN DEN BERG, M.J. Inventory of documents - VAN DEN BERG, M.J. (ARCA, 2018)
Private papers of M.J. van den Berg, Labour Party MP Krugersdorp [1934-1948]; National Party MP Krugersdorp [1948-1970].
COVERAGE 1930, 1964-1965; 1 File; 0,11 Metre.
Keywords: VAN DEN BERG, M.J.; Inventories; Politicians; National Party